The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11244-008-9163-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reactor Configuration on the Selective Oxidation of Glycerol over Au/TiO2

Abstract: The oxidation of glycerol by molecular oxygen in the aqueous phase over Au/TiO 2 was investigated in both a batch reactor and a continuous upflow fixed bed reactor. The effects of catalyst particle size, gas flow rate, liquid flow rate, reaction temperature, dioxygen pressure, and solution pH were examined in the fixed bed system. The unique hydrodynamics of the fixed bed system allowed for secondary oxidation products such as tartronic acid and oxalic acid to form in substantial amounts, which contrasts the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 16 publications
4
67
2
Order By: Relevance
“…By performing the heterogeneously catalyzed aerobic oxidation of glycerol in flow, [272][273][274] high product selectivity could be achieved over a Au/TiO 2 catalyst packed in a milli-reactor (d C = 4 mm) using water as solvent in the presence of base (0.1-0.6 M NaOH) ( Table 5, entry 8). By performing the heterogeneously catalyzed aerobic oxidation of glycerol in flow, [272][273][274] high product selectivity could be achieved over a Au/TiO 2 catalyst packed in a milli-reactor (d C = 4 mm) using water as solvent in the presence of base (0.1-0.6 M NaOH) ( Table 5, entry 8).…”
Section: Oxidation Of Glycerol To C 3 Aldehydes and C 2 /C 3 Acidsmentioning
confidence: 99%
“…By performing the heterogeneously catalyzed aerobic oxidation of glycerol in flow, [272][273][274] high product selectivity could be achieved over a Au/TiO 2 catalyst packed in a milli-reactor (d C = 4 mm) using water as solvent in the presence of base (0.1-0.6 M NaOH) ( Table 5, entry 8). By performing the heterogeneously catalyzed aerobic oxidation of glycerol in flow, [272][273][274] high product selectivity could be achieved over a Au/TiO 2 catalyst packed in a milli-reactor (d C = 4 mm) using water as solvent in the presence of base (0.1-0.6 M NaOH) ( Table 5, entry 8).…”
Section: Oxidation Of Glycerol To C 3 Aldehydes and C 2 /C 3 Acidsmentioning
confidence: 99%
“…92,93 Davis and co-workers demonstrated that Au was more active than Pd and Pt with the use of high base concentration, whereas the activity of bimetallic Pd/Au systems was significantly lower than that of monometallic Au but led to greater formation of glyceric acid. 94 It was also demonstrated that hydrogen peroxide was formed during glycerol oxidation and its formation was associated with an increased presence of base in solution; 95 the H 2 O 2 formed can cause carbon-carbon bond cleavage and increase the formation of by-products during oxidation reactions.…”
Section: Selective Oxidation Of Alcohols Derived From Biomassmentioning
confidence: 99%
“…When the support was neutral or alkaline, the supported Rh catalyst was more active (222). In addition, it was recently found that Au-Pd alloys/TiO 2 catalysts appeared peculiarly active (225,226). For these phenomena, the reasons were often attributed to the geometric and electronic state on the support surface and the metal-support interactions (227).…”
Section: Glycerol To Glyceric Acidmentioning
confidence: 99%